2012
DOI: 10.15282/jmes.2.2012.8.0019
|View full text |Cite
|
Sign up to set email alerts
|

Steady State Vortex Structure of Lid Driven Flow Inside Shallow Semi-Ellipse Cavity

Abstract: In this paper, the lid driven cavity flow inside a semi-ellipse shallow cavity was simulated using the stream function vorticity approach emphasising the non-uniform grid method. Three aspect ratios of 1:4, 1:3 and 3:8 were simulated using laminar flow conditions (range of Reynolds numbers of 100-2000). Primary and secondary vortexes were monitored extensively through centre vortex location, streamlines pattern and peak stream function values. Secondary vortexes developed at Re 1500 for the aspect ratio of 1:4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…The flow inside a square cavity has been widely used to demonstrate fluid flow using simple geometry. The flow structure in a one-sided lid-driven cavity problem has been reported by many researchers (Ghia, Ghia, & Shin, 1982;Idris, Ammar, Tuan Ya, & Amin, 2013;Idris, Irwan, & Ammar, 2012;Musa, Abdullah, Azwadi, & Zulkifli, 2011;Rosdzimin, Zuhairi, & Azwadi, 2010;Sidik & Attarzadeh, 2011). Later, research on different cavity geometries has been reported, such as a deep cavity (Patil, Lakshmisha, & Rogg, 2006), semi-circular cavity (Yang, Shi, Guo, & Sai, 2012), trapezoidal cavity (Zhang, Shi, & Chai, 2010) and triangular cavity (González, Ahmed, Kühnen, Kuhlmann, & Theofilis, 2011).…”
Section: Introductionmentioning
confidence: 80%
“…The flow inside a square cavity has been widely used to demonstrate fluid flow using simple geometry. The flow structure in a one-sided lid-driven cavity problem has been reported by many researchers (Ghia, Ghia, & Shin, 1982;Idris, Ammar, Tuan Ya, & Amin, 2013;Idris, Irwan, & Ammar, 2012;Musa, Abdullah, Azwadi, & Zulkifli, 2011;Rosdzimin, Zuhairi, & Azwadi, 2010;Sidik & Attarzadeh, 2011). Later, research on different cavity geometries has been reported, such as a deep cavity (Patil, Lakshmisha, & Rogg, 2006), semi-circular cavity (Yang, Shi, Guo, & Sai, 2012), trapezoidal cavity (Zhang, Shi, & Chai, 2010) and triangular cavity (González, Ahmed, Kühnen, Kuhlmann, & Theofilis, 2011).…”
Section: Introductionmentioning
confidence: 80%
“…Reference such as F. C.G.A. Nicolleau [3] used different pattern in their experiment, they found that pressure drop from a lower value to higher value by increasing the distance. The blockage ratio used in their experiment is 33.6%.…”
Section: Fractal Patternmentioning
confidence: 99%
“…First and second order derivatives of the non-uniform grid approximation were used and represented by the following equations (Idris et al, 2012) which were first discovered by (Veldman & Rinzema, 1992):…”
Section: Mathematical Modelmentioning
confidence: 99%
“…A non-uniform grid with the finite difference method has never been tested before, to the authors' knowledge after thorough research. However, while there is already a report based on this method, it is applied to an elliptical shaped lid-driven cavity flow (Idris, Ammar, & M Irwan, 2012). Thus, in this study a nonuniform grid and finite difference method will be applied to a semi-circular cavity to obtain validation, and once this is completed, the transient behavior of the streamline and vorticity contour will be studied until the steady state is achieved.…”
Section: Introductionmentioning
confidence: 99%